Perbandingan Pertumbuhan Aspergillus flavus Pada Media Filtrat Bekatul Dengan Berbagai Variasi Konsentrasi - Sa’adah Siregar; Vincentia Ade Rizky; Syukurin Juliani Gulo (SEHATI: Jurnal Kesehatan, 2025)
Mushrooms play a lot of role in life, both beneficial and detrimental. Certain types of fungi are capable of producing a toxic organic compound called mycotoxin. The mycotoxin produced by Aspergillus flavus is known as aflatoxin. The mushroom growth medium that is often used is SDA (Sabouraud Dextrose Agar). The composition of SDA media is peptone mycology, sugar, agar. The content of rice bran is carbohydrates, protein, water, and agar. The purpose of the study was to determine the comparison of growth diameter and effectiveness of Aspergillus flavus  concentration on bran filtrate media with various concentration variations. The method used in this study was experimental with inoculation of Aspergillus flavus fungi with a single dot method. The average colony diameter concentrations of 5%, 10%, 15% and 20% were 5.3 mm, 8.4 mm, 11.4 mm, and 16.5 mm. On SDA media  the average colony diameter is 17.6 mm. The concentration of bran filtrate media that is close to SDA  media is a concentration of 20%.  The results  of the One Way ANOVA  test showed a significant difference in the growth of Aspergillus flavus between various variations in bran filtrate concentration obtained a sig value of 0.000 less than 0.05. The conclusion of  data analysis using the One Way ANOVA  test was a significant difference in the growth of Aspergillus flavus between various variations in bran filtrate concentration obtained a sig value of 0.000 less than 0.05. In the bonfferoni test results, it was found that a concentration of 20% had similarities or significance to the positive control media of natural resources with a value of (p) 0.331 more than 0.05 which means that there is no significant difference between bran filtrate media at a concentration of 20% with positive control media  of natural resources